2016
DOI: 10.5194/hess-20-4177-2016
|View full text |Cite
|
Sign up to set email alerts
|

Describing the interannual variability of precipitation with the derived distribution approach: effects of record length and resolution

Abstract: Abstract. Interannual variability of precipitation is traditionally described by fitting a probability model to yearly precipitation totals. There are three potential problems with this approach: a long record (at least 25-30 years) is required in order to fit the model, years with missing rainfall data cannot be used, and the data need to be homogeneous, i.e., one has to assume stationarity. To overcome some of these limitations, we test an alternative methodology proposed by Eagleson (1978), based on the der… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(36 reference statements)
2
2
0
Order By: Relevance
“…Similar studies highlighting the influence of the MIT criterion on the rainfall properties have been reported in other countries, e.g. see Haile et al (2011);Medina-Cobo et al (2016); Meier et al (2016) and Molina-Sanchis et al (2016).…”
Section: Introductionsupporting
confidence: 84%
“…Similar studies highlighting the influence of the MIT criterion on the rainfall properties have been reported in other countries, e.g. see Haile et al (2011);Medina-Cobo et al (2016); Meier et al (2016) and Molina-Sanchis et al (2016).…”
Section: Introductionsupporting
confidence: 84%
“…On the other hand, RCMs showed good simulation for both maximum and minimum temperature during the temperate (dry) season than wet seasons. This shows the satellite extraction tendency and performance of RCM's in capturing precipitation and temperature was mostly rely on the seasons where the climate variables are expected to be reproduced which also concluded by (Meier et al, 2016). In this case, both RACMO22T and RCA4 have shown better performance in capturing the inter-annual variability of precipitation in all-season than others.…”
Section: Inter-annual Variability Of Precipitations and Temperature Anomaliessupporting
confidence: 53%
“…Perona et al (2013) obtained analytical expressions for probability distribution functions of optimally allocated river flows to human activity and the environment, using the derived distribution approach. Meier et al (2016) estimated the probability distribution function of annual rainfall from short-term records and showed that the derived distribution approach can be used for datasets where information is missing in certain years.…”
Section: Uncertainty Analysis and Numerical Derived Distribution Methodsmentioning
confidence: 99%